Ответ(ы) на вопрос:
Преобразуем уравнение так:
[latex] \frac{1}{log_{ \frac{1}{x}}2 } + \frac{1}{2log_{ \frac{1}{x}}2 } + \frac{1}{3log_{ \frac{1}{x}}2 } = -\frac{11}{2} [/latex]
Пишем ОДЗ: x>0 ∩ x≠1
Теперь домножаем уравнение на [latex]6log_{ \frac{1}{x}}2 \neq 0[/latex] и решаем:[latex] \frac{1}{log_{ \frac{1}{x}}2 } + \frac{1}{2log_{ \frac{1}{x}}2 } + \frac{1}{3log_{ \frac{1}{x}}2 } = -\frac{11}{2} \\ 6+3+2= -33log_{ \frac{1}{x}}2 \\ -33log_{ \frac{1}{x}}2=11 \\ log_x2= \frac{1}{3} \\ x^ \frac{1}{3} =2 \\ x=8[/latex]
Не нашли ответ?
Похожие вопросы